Harry S. Wragge AM (1929-2023): A Major Contributor to Australian Telecommunications - Gerrand, Peter (Journal of Telecommunications and the Digital Economy, 2023)
Harry Stewart Wragge (23 November 1929–31 July 2023), Director of the Telecom (later Telstra) Research Laboratories (TRL) in Melbourne from 1985 to 1992, was a leading Australian research engineer. He catalysed the evolution of the public switched telephone network in Australia from its analogue, electromechanical form in the 1950s and 1960s to the digital, computer-controlled circuit-switched network of the 1980s and 1990s. His own research work was famous for his IST (integrated switching and transmission) project, building the first computer-controlled, integrated digital switch in the world to handle commercial telephone traffic (from 1974 to 1978). He also provided major support to telecommunications research at several Australian universities. His many contributions were recognized by honours from the Australian Government, Melbourne and Monash universities, the Pearcey Foundation, the Telecommunications Society of Australia and the City of Frankston.